2022
DOI: 10.3390/su14138190
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Modified Biochar Impacts on Soil Properties and Biochemical Characteristics of Crops Grown in Saline-Sodic Soils

Abstract: Soil salinity and sodicity is a potential soil risk and a major reason for reduced soil productivity in many areas of the world. This study was conducted to investigate the effect of different biochar raw materials and the effects of acid-modified biochar on alleviating abiotic stresses from saline-sodic soil and its effect on biochemical properties of maize and wheat productivity. A field experiment was conducted as a randomized complete block design during the seasons of 2019/2020, with five treatments and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 83 publications
2
12
0
1
Order By: Relevance
“…Therefore, any factor that improves plant growth increases the plant's dry matter. Some studies have reported neutral or negative effects of biochar on plant performance [43,44]. However, many studies have suggested that increased plant growth after applying modified biochar could be due to improvements in soil CEC [30], Na+/K+ ratio under saline conditions [41], photosynthesis, nutrient uptake and soil physical and chemical properties [24,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any factor that improves plant growth increases the plant's dry matter. Some studies have reported neutral or negative effects of biochar on plant performance [43,44]. However, many studies have suggested that increased plant growth after applying modified biochar could be due to improvements in soil CEC [30], Na+/K+ ratio under saline conditions [41], photosynthesis, nutrient uptake and soil physical and chemical properties [24,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, improved soil structure facilitates the migration of salts to the lower soil layer. It prevents their upward movement because of evaporation, ultimately decreasing soil EC in the arable layer (El‐Sharkawy et al., 2022). Compared with the original BC, modified BC often has a larger surface area and more adsorption sites and has stronger adsorption of salt.…”
Section: Improvement Effect and Mechanisms Of Modified Bc On Saline‐a...mentioning
confidence: 99%
“…El‐Sharkawy et al. (2022) utilized BC modified with acid and rich in oxygen‐containing functional groups to amend salt‐affected soils. As a result, the CEC of the soil layer was improved to different extents, with a better effect than unmodified BC.…”
Section: Improvement Effect and Mechanisms Of Modified Bc On Saline‐a...mentioning
confidence: 99%
“…Adanya pengurangan ini tentunya berdampak tidak langsung terhadap pengurangan cekaman ditunjukkan dengan penurunan akumulasi prolin. Biochar yang dimodifikasi asam dapat dianggap ramah lingkungan, lebih murah dan pilihan yang efektif dalam mengurangi tekanan abiotik dari tanah salin-sodik dan secara positif mempengaruhi jagung dan produktivitas gandum (El-Sharkawy et al, 2022).…”
Section: Uji Aplikasi T Harzianum Dan Biochar Sekam Padi Pada Berbaga...unclassified